(untitled) - Bayes, Steve, 1959- (Boston, 2000)
The Avid Media Composer, Avid Xpress and Avid Symphony are the most widely used nonlinear editing systems by professionals in the film and video industries. Based on his experience teaching countless seminars around the world on the Avid Media Composer, Avid Symphony and Avid Xpress, Steve Bayes has written the most comprehensive manual for nonlinear digital editing on these Avid editing systems. This handbook is now revised throughout to reflect recent upgrades to these systems and the third edition covers Symphony 2.1, Media Composer 9.1 and Avid Xpress 3.1, as well as earlier versions. Written for the reader who already has a basic knowledge of the editing systems, this book moves beyond an introduction to the professional Avid editing systems and focuses on strategies, techniques, and troubleshooting. The Avid Handbook covers the basics of working with effects, rendering, and graphics and discusses the more abstract issues of workflow and organization of different types of editing projects. The book discusses frequently made mistakes, common technical problems,and how they can be avoided. In addition, there is an in depth explanation of Symphony color correction, 24 p and other new features and efficiencies in the latest software versions from Avid. The Avid Handbook discusses techniques for Windows NT users, including the most complete description of the offline to online workflow using Avid systems.
Keywords: Motion pictures,Video tapes; Editing,Data processing,Editing,Data processing